Implementation of Digitalization Marketing for UMKM in Manarap Lama Village - Sari, Raihanah; Nugroho Putro, Herry Porda; Subiyakto, Bambang; Rusmaniah, Rusmaniah; Suwarjo, Suwarjo; Awaliyah, Hijatul (Universitas Lambung Mangkurat, 2024)
Village Manarap Lama is one of the sasirangan producing villages, which is why this village is often also called sasirangan village. Results processed sasirangan usually for sale traditionally through several shops located in Manarap village itself starting from old, middle and new Manarap. This of course makes the scope of sales narrow and only buyer Which come To the store just Which know product they And the impact to income UMKM Alone Which No increase, so that required a solution in the form of training on digital marketing so that UMKM from Sasirangan village in Manarap Lama village can introduce their products to potential consumers both online and online. online or offline with the aim of getting far-reaching benefits more big from previously. Activity devotion done in a way stare advance directly with MSME actors in Sasirangan village in Manarap Lama Village, Banjar Regency. They given training menegai application digitalization marketing covers sales via social media such as WhatsApp, Twitter, Instagram, Facebook and marketplace, as well as creating interesting videos to introduce their products with help a blogger. Results activity This form making website by representatives of the Manarap Lama Village community which contains marketing of their products form Sasirangan Cloth, Good Which Still in the form of raw materials nor Sasirangan Cloth Which Already processed into clothes.